Development of researching skills and meaningful learning in language and Literature Students - Rodríguez-Espinoza, Zenith V. (2021)
This research was developed with the aim of determining the relationship between the development of researching skills and meaningful learning in terms of understanding and solving problems in students of the Specialty of Language and Literature of the Faculty of Educational Sciences of the Universidad Nacional “Hermilio Valdizán”, 2019. Also, the method that was used for this research is the Descriptive, as well as the design used is the Correlational and the type of research, applied. The Faculty of Educational Sciences of the Universidad Nacional “Hermilio Valdizán” – UNHEVAL was had as population. In addition, a documentary review on research and a survey for collecting of necessary information had to be conducted. In conclusion, the results of the research have confirmed the general hypothesis: There is a significant relationship between the development of research skills and meaningful learning in terms of understanding and solving problems in students of the Specialty of Language and Literature of the Faculty of Educational Sciences of the Universidad Nacional “Hermilio Valdizán”, 2019, as 40%of students were observed to have significant good learning during the study group test, 43% have regular meaningful learning, 17% have significant low learning, and 0% have very low significant learning in understanding and solving problems in Language and Literature Specialty students , 2019.